COMPARISON BETWEEN ISLAMIC LAWS AND PRIVATE INTERNATIONAL LAWS: JURISDICTIONAL MATTERS OF SUCCESSION - Dr Sheikh Muhammad Adnan; Abid Hussain Shah; Khurram Baig, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
Sharia in Islam, Halakha in Judaism, and canon law in some Christian communities are the three primary types of religious law. In some circumstances, they are meant just as moral instruction for individuals, while in others, they serve as the foundation for a country's legal system.  In our study, we compare common law standards systems to succession and private law jurisdiction. Firstly, The Study tries to brief Islamic laws regarding succession and their steps of calculations, exceptions, and non-Muslim status. Secondly, discuss civil laws regarding succession and the concept of universal succession. Finally, the Study focuses on the Jurisdiction of Private International Law. In this study, we used a descriptive method of research. In many legal systems, private international law rules should be seen as a substantial step toward conflict of law control, despite any faults. It meets several international standards in this field and will make significant progress in regulating private international law.